BUiD Doctoral Research Conference 2023 Multidisciplinary Studies - Al Marri, Khalid; Mir, Farzana Asad.; David, Solomon Arulraj; Al-Emran, Mostafa; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This open access book presents selected contributions on a wide range of scientific and technological areas originating from the BUiD Doctoral Research Conference (BDRC 2023). It discusses the following topics: project management, macroeconomic factors, Fourth Industrial Revolution, agility, multiculturalism, diversity, inclusion, leadership, language, discourse analysis, curriculum, critical thinking, programming, online learning, and natural ventilation. The contributions reflect the multifaceted nature of the research in three academic disciplines, i.e., humanities, formal science, and applied science. This publication shares with its readers genuine research studies and reflections from practitioners on the current practice and understanding in the three academic disciplines. The significant findings of these studies have considerable educational, industrial, and economic implications. This is an open access book.
Critically Describing the Effectiveness of Antibullying Interventions Used at Schools -- The Impact of Job Satisfaction on Teachers$1 (BPerformance in the UAE -- Highlighting the Impacts of Parents$1 (BBeliefs on Students$1 (BEducation -- Jordanian Expatriates$1 (BFamily Language Policy in Dubai -- The impact of bullying in an inclusive classroom among students of ASD and peers in social development and academic performance in the UAE -- The Impact of the Zone of Proximal Development Concept (Scaffolding) on the Students Problem Solving Skills and Learning Outcomes -- An Investigation of the Development and Implementation of Teacher's Licensing in Saudi Arabia Based on Local Stakeholders' Perceptions, Compared with International and Regional Practices -- The Challenges of Implementing the Emirates Standardized Test as a Proficiency Test in the UAE: An Exploratory Study -- The relationship between the frequency and the range of morphemes used in students$1 (Bessays and essay scores in an American school in Dubai -- The Implementation of Critical Thinking Skills in American Curriculum Schools in Sharjah: A Study on Science Teachers' Approach and Academic Standards.s
Keywords: Science -- Study and teaching; Sociology; Economic development; Science Education; Sociology; Economic Growth